Perspektif Corporate Social Responsibility Di Perusahaan Keluarga: survei Perusahaan Keluarga Di Semarang - Ranto P Sihombing; Monika Palupi; Stephana Dyah Ayu; vena Purnamasari; Clara Susilawati (Conference In Business, Accounting, And Management (CBAM), 2012)
The study conducted about Corporate Social Responsibility (CSR) has been done, namely Sembiring (2005) that examined the characteristics of corporate and social responsibility disclosure on Indonesia Stock Exchange. In addition, Anggraini (2006) has also examined the factors of social disclosure on companies listed on the Indonesia Stock Exchange. Both studies were conducted using financial data public company are easily obtained and analyzed. However, research on family companies which aims to find out if companies implement CSR and what are the factors that drive companies to implement CSR has never been done. It also encourages researchers to investigate how the application of social and environmental responsibility in the family company. The result of this research, it was obtained, first, the family company in Semarang has implemented CSR from the aspect of profit, planet, people, and procedural aspects. Companies have set aside some profit for CSR. The company also has made programs that positively impact the environment, and has had a policy that protects the rights of employees. But in terms of not well-monitored implementation yet because not involve a third party. Secondly, the reason companies implement CSR diverse. Mostly, they did because business ethics. The implications of this study are the results of this study can be used as the basis for regulatory decision-making in this case local governments to develop any activity that may be required for companies to conduct and report on CSR activities, especially in the family company. With hoping isto create harmonization between the company, the environment and stakeholders in order to realize sustainable development.Keywords: corporate social responsibility, family companies, business ethics, harmonization, sustainable development